Comprehensible legal texts - utopia or a question of wording? On processing rephrased German court decisions - Hansen, Sandra; Dirksen, Ralph; Küchler, Martin; Kunz, Kerstin; Neumann, Stella (HERMES - Journal of Language and Communication in Business, 2006)
This paper presents a study on the comprehensibility of rephrased syntactic structures in German court decisions. While there are a number of studies using psycholinguistic methods to investigate the comprehensibility of original legal texts, we are not aware of any study looking into the effect resolving complex structures has on the comprehensibility. Our study combines three methodological steps. First, we analyse an annotated corpus of court decisions, press releases and newspaper reports on these decisions in order to detect those complex structures in the decisions which distinguish them from the other text types. Secondly, these structures are rephrased into two increasingly simple versions. Finally, all versions are subjected to a self paced reading experiment. The ﬁndings suggest that rephrasing greatly enhances the comprehensibility for the lay reader.